The effect of copper oxide nanoparticle conjugated with lapatinib on breast cancer cell line and evaluating the effect of this nanoparticle on caspase 8 gene expression - Masoumeh Valizadeh Talarposhti; Ali Salehzadeh; Amir Jalali (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Breast cancer is a significant global cause of cancer-related mortality, highlighting the urgent need for new drugs to combat this prevalent disease. This study was designed to investigate the anticancer effect of copper oxide nanoparticles conjugated with lapatinib and its effect on the expression of the caspase-8 gene in a breast cancer cell line. Materials & Methods: Copper oxide nanoparticles were synthesized from a CuCl₂ solution, treated with D-glucose, and then linked to lapatinib. The physicochemical properties of the nanoparticles were analyzed using FT-IR, XRD, EDS, DLS, zeta potential measurement, and electron microscope imaging. The effect of the nanoparticles on the viability of breast cancer (MDA-MB-231) and normal (MRC-5) cells was evaluated using the MTT test, while the expression of the caspase-8 gene was measured via real-time PCR. Statistical differences were analyzed using one-way ANOVA in SPSS V.22, with a p-value less than 0.05 considered statistically significant. Results: The study found that copper oxide nanoparticles conjugated with lapatinib had a spherical morphology, a surface charge of -14 mV, and a particle size of 426.3 nm in aqueous medium. These nanoparticles had concentration-dependent inhibitory effects on cancer and normal cell lines, with a 50% inhibitory concentration of 75 and 120 μg/ml, respectively, and a 3.24-fold increase in caspase-8 gene expression. Conclusion: Copper oxide nanoparticles linked with lapatinib were more effective at stopping cancer cells than normal cells, and by boosting the levels of caspase-8, they trigger the external pathway of cell death in cancer cells.